2018
DOI: 10.1016/j.neuropsychologia.2018.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Mid-frontal theta activity is diminished during cognitive control in Parkinson's disease

Abstract: Mid-frontal theta activity underlies cognitive control. These 4-8 Hz rhythms are modulated by cortical dopamine and can be abnormal in patients with Parkinson's disease (PD). Here, we investigated mid-frontal theta deficits in PD patients during a task explicitly involving cognitive control. We collected scalp EEG from high-performing PD patients and demographically matched controls during performance of a modified Simon reaction-time task. This task involves cognitive control to adjudicate response conflict a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

28
175
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 105 publications
(205 citation statements)
references
References 49 publications
28
175
2
Order By: Relevance
“…Time-frequency and correlation results suggest the role of frontal theta in motor and cognitive and motor control systems (see figures 4 and 5), which are required to initiate and execute lower-body movements, 20,25 though frontal beta activity is mostly associated with motor control system. 21,22 As proposed by previous reports, frontal regions may play an important role in top-down signaling to guide adjustment of preparatory and execution plans during motor tasks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Time-frequency and correlation results suggest the role of frontal theta in motor and cognitive and motor control systems (see figures 4 and 5), which are required to initiate and execute lower-body movements, 20,25 though frontal beta activity is mostly associated with motor control system. 21,22 As proposed by previous reports, frontal regions may play an important role in top-down signaling to guide adjustment of preparatory and execution plans during motor tasks.…”
Section: Discussionmentioning
confidence: 99%
“…Mid-frontal theta-rhythms have been associated with cognitive control, and can be associated with impairments in cognitive control in PD patients. 20,25 Our past work has suggested that frontal theta-rhythms are not modulated by levodopa. 20 In our study, PDFOG+ patients had impaired cognitive control relative to PDFOG-patients and attenuated frontal theta-rhythms.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, although early increases in mPFC theta power and mPFC-STN phase synchrony may be considered anti-kinetic, later theta power increases in the STN may actually promote movement. Our inferences are drawn from data collected in patients with Parkinson’s disease, and so should be interpreted with caution as dopamine depletion and DBS surgery are known to alter the basal ganglia activity (Hammond et al, 2007; Singh et al, 2018). Nonetheless, we find that patterns of theta and beta band activity in the STN and mPFC play complementary, temporally sequenced roles in supporting different processes that together contribute to cognitive control.…”
Section: Discussionmentioning
confidence: 99%
“…(a) Frontal midline theta power is enhanced during the need for control, whereas mediolateral theta phase synchrony is proposed to reflect the communication of this need to lateral frontal areas (Cavanagh & Frank, ). (b) Different psychiatric and neurological diseases characterized by frontal dysfunction have different patterns of theta band dynamics; 1 Cavanagh, Meyer, et al (); 2 Singh, Pirio Richardson, Narayanan, and Cavanagh (); 3 Ryman et al (). (c) Using features identified in the studies in (b), receiver operating characteristic (isosensitivity) plots can be created to determine the classification success against a control group.…”
Section: Electrophysiology As a Hub For The Neural Sciencesmentioning
confidence: 99%